The furanosidic scaffold of d-ribose: a milestone for cell life. (7th November 2019) - Del-Corso, Antonella; Cappiello, Mario; Moschini, Roberta; Balestri, Francesco; Mura, Umberto; Ipata, Piero Luigi
Abstract : The recruitment of the furanosidic scaffold of ribose as the crucial step for nucleotides and then for nucleic acids synthesis is presented. Based on the view that the selection of molecules to be used for relevant metabolic purposes must favor structurally well-defined molecules, the inadequacy of ribose as a preferential precursor for nucleotides synthesis is discussed. The low reliability of ribose in its furanosidic hemiacetal form must have played ab initio against the choice of d -ribose for the generation of d -ribose-5-phosphate, the fundamental precursor of the ribose moiety of nucleotides. The latter, which is instead generated through the 'pentose phosphate pathway' is strictly linked to the affordable and reliable pyranosidic structure of d -glucose.